Understanding Ustilago maydis Infection of Multiple Maize Organs - Alex C Ferris; Virginia Walbot (Journal of Fungi, 2020)
Ustilago maydis is a smut fungus that infects all aerial maize organs, namely, seedling leaves, tassels, and ears. In all organs, tumors are formed by inducing hypertrophy and hyperplasia in actively dividing cells; however, the vast differences in cell types and developmental stages for different parts of the plant requires that U. maydis have both general and organ-specific strategies for infecting maize. In this review, we summarize how the maize–U. maydis interaction can be studied using mutant U. maydis strains to better understand how individual effectors contribute to this interaction, either through general or specific expression in a cell type, tissue, or organ. We also examine how male sterile maize mutants that do not support tumor formation can be used to explore key features of the maize anthers that are required for successful infection. Finally, we discuss key unanswered questions about the maize–U. maydis interaction and how new technologies can potentially be used to answer them.